Isolation and Characterization of Ethyl Acetate Fraction from Abroma augusta L as an Anti-Inflammatory Agent - Latief, Madyawati; Tarigan, Indra Lasmana; Muhaimin, Muhaimin; Amanda, Hilda; Yulianti, Nike Desvi (Makara Journal of Science, 2021)
Abroma augusta is a bush plant that lives on the edge of the river. This plant is commonly used as an anti-inflammatory drug for joints and broken bones. It contains several secondary metabolites, such as alkaloids, triterpenoids, steroids, and flavonoids, which exhibit anti-inflammatory activity. UV-visible (UV-Vis) spectrophotometry of isolate 1.3 indicated absorption at a maximum wavelength of 282 nm. The wavelength suggested that the electron transition π–π* is the absorption of UV spectra typical for triterpenoid compounds that have chromophores in the form of non-conjugated double bonds. FT-IR spectrophotometer characterization data from isolate 1.3 revealed the presence of triterpenoid compounds having carboxyl groups C-O (ester), C-(CH3)2 (gem-dimethyl), carbonyl C = O esters, and C-H (alkyl). Analyses of UV-Vis, FT-IR, GC-MS, 1H-NMR, and 13C-NMR spectra showed that the compound obtained was the triterpenoid β-amyrin. Activity test demonstrated that isolate 1.3 with a 10 mg dose showed stronger anti-inflammatory activity than the positive control of sodium diclofenac.